Neurofilament ELISA validation - Petzold, Axel; Jarius, Sven; Wildemann, Brigitte (Journal of immunological methods, 2010)
Background - Neurofilament proteins (Nf) are highly specific biomarkers for neuronal death and axonal degeneration. As these markers become more widely used, an inter-laboratory validation study is required to identify assay criteria for high quality performance. - Methods - The UmanDiagnostics NF-light ®enzyme-linked immunoabsorbent assays (ELISA) for the neurofilament light chain (NfL, 68kDa) was used to test the intra-assay and inter-laboratory coefficient of variation (CV) between 35 laboratories worldwide on 15 cerebrospinal fluid (CSF) samples. Critical factors, such as sample transport and storage, analytical delays, reaction temperature and time, the laboratories' accuracy and preparation of standards were documented and used for the statistical analyses. - Results - The intra-laboratory CV averaged 3.3% and the inter-laboratory CV 59%. The results from the test laboratories correlated with those from the reference laboratory (R=0.60, p<0.0001). Correcting for critical factors improved the strength of the correlation. Differences in the accuracy of standard preparation were identified as the most critical factor. Correcting for the error introduced by variation in the protein standards improved the correlation to R=0.98, p<0.0001 with an averaged inter-laboratory CV of 14%. The corrected overall inter-rater agreement was subtantial (0.6) according to Fleiss' multi-rater kappa and Gwet's AC1 statistics. - Conclusion - This multi-center validation study identified the lack of preparation of accurate and consistent protein standards as the main reason for a poor inter-laboratory CV. This issue is also relevant to other protein biomarkers based on this type of assay and will need to be solved in order to achieve an acceptable level of analytical accuracy. The raw data of this study is available online.